Photochemical Reactions for the Synthesis of Six-Membered O-Heterocycles - Kaur, Navjeet (Current Organic Synthesis, 2018)
Background: The chemists have been interested in light as an energy source to induce chemical reactions since the beginning of the scientific chemistry. This review summarizes the chemistry of photochemical reactions with emphasis of their synthetic applications. The organic photochemical reactions avoid the polluting or toxic reagents and therefore offer perspectives for sustainable processes and green chemistry. In summary, this review article describes the synthesis of a number of six-membered O-heterocycles. Objective: Photochemistry is indeed a great tool synthetic chemists have at their disposal. The formation of byproducts was diminished under photochemical substrate activation that usually occurred without additional reagents. Photochemical irradiation is becoming more interesting day by day because of easy purification of the products as well as green chemistry. Conclusion: This review article represents the high applicability of photochemical reactions for organic synthesis and research activities in organic photochemistry. The synthesis of heterocyclic molecules has been outlined in this review. Traditional approaches require expensive or highly specialized equipment or would be of limited use to the synthetic organic chemist due to their highly inconvenient approaches. Photochemistry can be used to prepare a number of heterocycles selectively, efficiently and in high yield.
Keywords: photochemical